MARBA’ FI HUKM AN-NIKAH MANUSCRIPT BY SYEIKH 'ABBAS AL-'ASYI' (TEXT EDITING AND STUDY OF CENTRAL IDEA) - Amar Makruf; Nurdin AR; Ruhamah (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2022)
One of the 19th-century Malay-language Arab-Jawi manuscripts that contains the fiqh knowledge is the Marba’ Fi Hukm An-Nikah manuscript. The aim behind this study and its goal are to learn more about the edited text and the manuscript's key concepts. Because comparing the texts is an objective process, the research methodology involves philological analysis. There were just two manuscript texts discovered after searching the document. The first manuscript, which serves as the basis for comparison, is in the Pedir Museum's collection and has the inventory number MS-PM-0489/2020. The second manuscript, which serves as the basis for comparison, is in the Aceh State Museum's collection and has the inventory number 07 809. The text MS-PM-0489/2020 was chosen since the quality is higher with intact pages. The four major schools of thought's perspectives (mazhab) on the rules governing marriage are the text's main focus. The results of this study reveal that two things are necessary: first, a text that has been edited and given a critical edition; and second, it is essential to fully comprehend the manuscript Marba' Fi Hukm An-Nikah, which contains Islamic teachings on the science of fiqh. The book contains writings on a wide range of subjects, including talaq, fasakh law, taqlid law, and marriage and all themes related to marriage.